Smoking cessation attempts: is it useful to treat hard core smokers?. Issue 1 (December 2016) - Joly, B.; D'Athis, P.; Gerbaud, L.; Hazart, J.; Perriot, J.; Quantin, C.
Abstract Background Hard core smokers have been studied in many countries but only a few trials have compared the effectiveness of smoking cessation with other smokers. The objective of this study was to compare the frequencies of success in smoking cessation between hard-core smokers and other smokers. Methods Data were collected in Clermont-Ferrand from the Emile Roux dispensary 'Pneumology and Tobaccology Centre' between 1999 and 2009. Assistance with smoking cessation was proposed to 1367 patients but only 1296 patients were included: 219 HCS and 1077 other smokers. Smoking cessation was considered a success when patients were abstinent 6 months after the beginning of cessation. The profiles of the two types of smokers were compared using Chi square test and Student's t test. Multivariate logistic regression was used to investigate the association between the smoking cessation result and the type of smokers. Results HCS more frequently consumed other psychoactive substances (41.1 % vs 25.7 % for other smokers;p  < 0.001). Current depression was more frequent in HCS (46.6 % vs 34.8 % for other smokers;p  = 0.001). Smoking cessation was less frequent in HCS (45.2 % vs 56.5 % for other smokers ;p  = 0.002). In multivariate analysis, after controlling for other factors, the frequency of smoking cessation was not significantly associated with the type of smokers (p  = 0.47). After limiting to initial factors (present before the beginning of smoking cessation), the frequency of smoking cessation was still not significantly associated with the type of smokers (p  = 0.78). Conclusion Smoking cessation is possible for hard core smokers, who should be treated as other types of smokers taking into account other factors:the problem is how to encourage them to try to stop smoking.